Case Report: Management of a pregnancy complicated by a symptomatic macroprolactinoma - Topis, Spyridon; Christodoulaki, Kalliopi; Riga, Maria; Arkoulis, Ioannis; Karampitsakos, Theodoros; Sidiropoulou, Tatiana; Drakakis, Peter; Potiris, Anastasios; Stavros, Sofoklis (Frontiers in Medicine, 2025)
BackgroundProlactinomas are the most common functional pituitary adenomas and may lead to infertility, visual field defects, and neurological impairment. Pregnancy poses unique challenges to women with macroprolactinomas due to the potential for tumor enlargement under the influence of gestational hormonal changes.CaseWe present the case of a 40-year-old woman who conceived through in vitro fertilization (IVF) and presented at 38 + 3 weeks of gestation with new-onset diplopia. The magnetic resonance imaging (MRI) revealed a 29-mm hemorrhagic macroprolactinoma causing compression of the optic chiasm. The tumor had previously been asymptomatic and untreated. Management was undertaken by a multidisciplinary team including obstetricians, endocrinologists, neurosurgeons, and anesthesiologists. An elective cesarean section was performed under general anesthesia with careful attention to intracranial pressure control and hemodynamic stability.OutcomeDelivery was uneventful, with no perioperative neurological or anesthetic complications. The patient was discharged in good general condition and commenced long-term dopamine agonist therapy, with planned close endocrinological and neurosurgical follow-up.ConclusionThis case highlights the importance of early diagnosis, individualized management, and multidisciplinary coordination in pregnant women with macroprolactinomas. Dopamine agonists remain the cornerstone of therapy and are generally safe during early pregnancy. Meticulous anesthetic planning is essential to optimize maternal and fetal outcomes.